PENANAMAN KARAKTER DAN KEAGAMAAN ANAK OLEH ORANG TUA ASUH PADA MTs BERBASIS PONDOK PESANTREN DI NGAWI - Fatqu Rois (STAINU Purworejo, 2021)
Family have core element parent and child. Parents have duty to be responsible to physical and psichological needs of their children. Many needs of family make effect to take action in running the economy, even have to go to big cities for get more results. child Children are entrusted to foster parents at the expense of time together with the nuclear family. All physical facilities are fulfilled, but most of the psychological needs in the form of morality and religion are secondary. Foster parents have a very important role in fostering the character and religion of children. Especially those who have a high responsibility for the trust given by the child's biological parents. Foster parents who are religiously obedient and mature in their thoughts are able to be a substitute for the child's biological parents so that the character and religious side of the child can be controlled properly.